1993
DOI: 10.1017/s0890037x00037982
|View full text |Cite
|
Sign up to set email alerts
|

Selective Torpedograss (Panicum repens) Control in Bermudagrass (Cynodonspp.) Turf

Abstract: Torpedograss has invaded fine turfgrasses in the Southern U.S. due to its tolerance to most commonly used turfgrass herbicides. Research was conducted to determine torpedograss and ‘Tifway’ bermudagrass tolerance to quinclorac and tank-mix combinations with other turf herbicides. Quinclorac rates in excess of 2.2 kg ai/ha were required for control (≥ 80%) of torpedograss. Sequential applications were more effective than single applications. Generally, sequential applications made 3 wk after the initial were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…It is one of the serious weeds characterized by its highly regenerative rhizomes, colonizing the crop fields and creating hazards to the farmers, causing great economic losses every year in the tropical and subtropical regions (Holm et al 1977; Peng 1984). Torpedograss is also a severe problem in golf courses in Florida, Texas, Hawaii, Europe, tropical Africa and tropical Asia (McCarty et al 1993; Hossain et al 1999). The weed produced approximately 3.2 kg m −2 of biomass within 1 year, which was caused by a severe competition with crops both above ground and underground in Okinawa, Japan (Hossain 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the serious weeds characterized by its highly regenerative rhizomes, colonizing the crop fields and creating hazards to the farmers, causing great economic losses every year in the tropical and subtropical regions (Holm et al 1977; Peng 1984). Torpedograss is also a severe problem in golf courses in Florida, Texas, Hawaii, Europe, tropical Africa and tropical Asia (McCarty et al 1993; Hossain et al 1999). The weed produced approximately 3.2 kg m −2 of biomass within 1 year, which was caused by a severe competition with crops both above ground and underground in Okinawa, Japan (Hossain 1999).…”
Section: Introductionmentioning
confidence: 99%
“…L.) and zoysiagrass ( Zoysia japonica Steud.) can be achieved using selective, post‐emergence herbicides such as quinclorac or trifloxysulfuron (1,3,20,21,24). However, no selective post‐emergence herbicides have been documented for the control of torpedograss in centipedegrass [ Eremochloa ophiuroides (Munro) Hack.]…”
Section: Torpedograss Infestation Of Warm‐season Turfgrassesmentioning
confidence: 99%
“…L.) and zoysiagrass (Zoysia japonica Steud.) can be achieved using selective, post-emergence herbicides such as quinclorac or trifloxysulfuron (1, 3,20,21,24 Herbicides can be an effective means for reducing weed infestations; however, increasing turfgrass vigor through implementation of cultural practices is considered an important component of any comprehensive weed control program (6,27). In a review of cultural management in turfgrass, Busey (2003) concluded optimal mowing heights and fertility reduce weed colonization and promote grass monocultures.…”
Section: Torpedograss Infestation Of Warm-season Turfgrassesmentioning
confidence: 99%
“…Approximately 3.2 kg m −2 of torpedograss biomass is produced in 1 year and this causes severe competition with the crops both above ground and underground (Hossain et al 1999a). This weed is a big problem in golf courses in Florida, Texas, Hawaii, southern Europe, Tropical Africa and Tropical Asia (McCarty et al 1993; Hossain et al 1999b). Torpedograss has been considered for use as pasture, and it may be used for soil erosion control (Holm et al 1977; Hossain 1999).…”
Section: Introductionmentioning
confidence: 99%